Liquid-liquid phase separation of telomeric nucleosome array is mediated by TRF2 - Neo, Qi Ying (Nanyang Technological University, 2022)
Telomeres, the ends of the chromosomes, have always been an interesting area of structural genomic research as they are known to play crucial roles in ageing and cancer. The organization of human telomeric chromatin has been implicated in its functional roles as telomeres are the protectors of the ends of chromosome. Shelterin, a six-protein complex, is found to be associated with telomeres. The complex comprises of TRF1, TRF2, TIN2, RAP1, TPP1 and POT1. In this paper, the effect of TRF2 on human telomeric chromatin was studied. To achieve this, full-length TRF2 and telomeric DNA templates comprising 10x157bp telomeric repeats (T10) has been expressed in E. coli and purified in large-scale. T10 nucleosome array was reconstituted with histone octamers tagged with different fluorescent tags, such that liquid-liquid phase separation (LLPS) of telomeric chromatin and its interaction with TRF2 can be studied. LLPS was conducted using confocal microscopy using different TRF2 to T10 nucleosome arrays ratios to understand its effect on telomeric chromatin behavior – if droplets were formed. Results suggests that TRF2 mediates inter- array interaction of the human telomeric chromatin to form droplets. This finding will pave way to understand the role TRF2 on telomeric chromatin in ageing and cancer.